2010
DOI: 10.1002/jcu.20752
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically guided percutaneous excision of clinically benign breast masses

Abstract: Percutaneous excision using a vacuum-assisted biopsy device is an alternative to surgical excision of benign breast masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…Our previous study which was about the treatment for the other benign breast lesions with VACB also demonstrated that clear edge was helpful for the complete excision of lesions. 20 Our study demonstrated that intraductal papilloma with branch involvement or calcification had a significantly lower excision rate than those without branch involvement or calcification. Studies reported that intraductal papilloma with branch involvement or calcification often means a higher invasiveness of the lesion.…”
Section: Lesion Characteristics and Histologic Features Cases (%)mentioning
confidence: 50%
See 1 more Smart Citation
“…Our previous study which was about the treatment for the other benign breast lesions with VACB also demonstrated that clear edge was helpful for the complete excision of lesions. 20 Our study demonstrated that intraductal papilloma with branch involvement or calcification had a significantly lower excision rate than those without branch involvement or calcification. Studies reported that intraductal papilloma with branch involvement or calcification often means a higher invasiveness of the lesion.…”
Section: Lesion Characteristics and Histologic Features Cases (%)mentioning
confidence: 50%
“…A lesion with a clear edge could provide a more clear view in the process of operation and is helpful for a complete excision. Our previous study which was about the treatment for the other benign breast lesions with VACB also demonstrated that clear edge was helpful for the complete excision of lesions …”
Section: Discussionmentioning
confidence: 90%
“…In 141 patients, more than 10 frustules were taken in an attempt to completely remove the lesion using VABB with an 11- or 8-gauge probe, but complete removal occurred only in 93 cases, while in the remaining 48 cases, after the ultrasound-guided follow-up 6 months later, minimum residue of the lesion was still present [17, 18, 19, 20]. …”
Section: Resultsmentioning
confidence: 99%
“…Among 27 PTs that were excised surgically, however, residual tumor was found in 15 (55.6%; 12 benign, 1 borderline and 2 malignant). Two previous studies reported that PTs exhibited no residual abnormality on US after US-VAE, but residual lesions were found in subsequent surgical excision (Wang et al 2011. Given these results and the association of residual tissue with local recurrence of PTs, subsequent surgical excision with a negative resection margin should be considered for PTs diagnosed after US-VAE (Jang et al 2012).…”
Section: Discussionmentioning
confidence: 87%
“…However, it has been found that complete removal based on US does not mean complete histologic removal and very small amounts of residual tumor may not be detected on US immediately after US-VAE (Wang et al 2011). During and immediately after US-VAE, it is difficult to confirm the status of an excised mass because of the physical change induced by biopsy and technical problems.…”
Section: Discussionmentioning
confidence: 97%